STUDENT COUNCIL AS A FORM OF SELF-GOVERNMENT - Pavel B. Dermer; Marina V. Dobrinets; Aleksandr M. Gofman (Высшее образование в России)
The article dwells on the activities of student self-government system at technical university. Self-government plays an important role in the process of specialists training as it allows to form students’ civic stand, commitment to preservation and augmentation of moral, cultural and human values, as well as to develop common cultural competence necessary to prepare future graduates. The work of student self-government at technical university has its own characteristics. Successful implementation of student self-government activities at technical university contributes significantly to the preparation of highly skilled, versatile developed specialist. The article describes the experience of the activities of student organizations at the Bauman Moscow State Technical University.